Agronomic performance of experimental super sweet corn hybrids - Gava,Emanuel (2021)
ABSTRACT Super sweet is classified as a special type of corn, due to the presence of genes which promote sugar accumulation in grains, significantly reducing starch content in the endosperm. This study aimed to evaluate the agronomic performance of experimental super sweet corn hybrids, carrying the gene shrunken-2, in order to identify and select promising genotypes for Southern Brazil. The experiments were carried out in two sowing seasons in 2017/18, in the experimental field of UNICENTRO, Guarapuava-PR, Brazil. Thirty-two experimental hybrids resulting from an 8x4 partial diallel among super sweet corn inbred lines from four distinct populations were evaluated along with two commercial hybrids (BRS Vivi and Tropical Plus) used as checks. Traits of agronomic and commercial interest were evaluated: male flowering (MF), husk covering index (HCI), yield of husked ears (YHE), grain yield (GY), commercial prolificacy (CPR), percentage of commercial ears (PCE), color (COL) and soluble solids (SS) of the grains. We verified significant differences among the experimental hybrids, except for COL. There was no significant effect of sowing season regarding to SS. Genotypes x seasons interaction was significant for YHE, GY, CPR, PCE and COL. There are promising experimental hybrids showing performances superior to commercial super sweet corn hybrids used in Brazil. The experimental hybrids D2-61 x D5-41 and D3-10 x D5-43 were superior to the other experimental genotypes. The experimental hybrid D2-61 x D5-41 shows potential to meet the demands of the current super sweet corn market.